Bacterial iron-oxide nanowires from biofilm waste as a new adsorbent for the removal of arsenic from water. Issue 7 (16th January 2017) - Andjelkovic, Ivan; Azari, Sara; Erkelens, Mason; Forward, Peter; Lambert, Martin F.; Losic, Dusan
Abstract : Biofilm waste material generated by the bacteria in the groundwater pipelines was found is composed of amorphous twisted iron-oxide nanowires which are shown to have considerable adsorption properties for removal As(iii ) and As(v ) ions from waters. Abstract : Biofilm, generated by the bacteria in the groundwater pumping system pipelines of the Salt Interception Scheme on the River Murray in South Australia is discarded as a waste material accumulated after periodic cleaning of the pipes. Structural and chemical composition characterizations confirm that this waste material is composed of amorphous twisted iron-oxide nanowires (ION), generated by bacteria, and they have a unique structure and properties. The adsorption performance of these iron-oxide nanowires for arsenic removal from water was evaluated to define their adsorption capacity for As(iii ) and As(v ) and kinetics. Obtained results demonstrate considerable adsorption properties of this waste biological material and suggest its promising application as a new and low-cost adsorbent for water treatment.